2020
DOI: 10.1021/acsanm.9b02395
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Incorporation-Induced SERS Enhancement in Silver Nanoparticle-Decorated ZnO Nanowires

Abstract: Surface-enhanced Raman spectroscopy (SERS) is a sensitive and nondestructive technique used for the detection of molecules, traditionally applied on noble-metal or semiconductor substrates. Point defect introduction has been applied to increase the enhancement of semiconductor templates due to more efficient charge transfer; however, they are still limited by low detection sensitivity and inferior SERS enhancement. Here we propose a universal approach of oxygen incorporation into metal oxide nanowire/metal nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Figure 5 c displays the effect of the annealing temperature of Ag/ZnO nanowires on the SERS spectra of (meso-tetra(N-methyl-4-pyridyl)porphine tetrachloride (TMPyP) molecules. A LOD of 100 nM is found for TMPyP molecules with Ag/ZnO nanowires annealed at 200 °C (see Figure 5 d) [ 86 ].…”
Section: Novelties On Plasmonic and Non-plasmonic Nanomaterials Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 c displays the effect of the annealing temperature of Ag/ZnO nanowires on the SERS spectra of (meso-tetra(N-methyl-4-pyridyl)porphine tetrachloride (TMPyP) molecules. A LOD of 100 nM is found for TMPyP molecules with Ag/ZnO nanowires annealed at 200 °C (see Figure 5 d) [ 86 ].…”
Section: Novelties On Plasmonic and Non-plasmonic Nanomaterials Fomentioning
confidence: 99%
“…( d ) SERS spectra of TMPyP recorded on Ag/ZnO nanowires annealed at 200 °C for various concentrations of TMPyP. Inset in ( d ) displays the whole spectrum with fluorescence signal that appears when the concentration is superior or equal to 10 −5 M. All the figures are reprinted (adapted) with permission from [ 86 ], Copyright 2020 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…In addition, the SERS effect is also very useful for studying the surface catalytic reactions in order to know their mechanism and their intermediate species involved in these reactions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In this SERS field, an alternative section has emerged named photo-induced enhanced Raman spectroscopy (PIERS), which gives the possibility of having supplementary chemical enhancement of the Raman signal compared to conventional SERS, by employing a photo-activated semiconductor substrate [ 17 , 18 , 19 , 20 ]. This supplementary chemical enhancement is due to the presence of surface oxygen vacancies (V ) created during the pre-irradiation of the semiconductor substrate by UV light [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this SERS field, an alternative section has emerged named photo-induced enhanced Raman spectroscopy (PIERS), which gives the possibility of having supplementary chemical enhancement of the Raman signal compared to conventional SERS, by employing a photo-activated semiconductor substrate [ 17 , 18 , 19 , 20 ]. This supplementary chemical enhancement is due to the presence of surface oxygen vacancies (V ) created during the pre-irradiation of the semiconductor substrate by UV light [ 17 , 18 , 19 , 20 ]. In the literature, it is well-reported that UV light can allow the creation of defects/vacancies in different materials (nanostructured or not), such as metal oxides [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], silicon dioxide [ 25 , 26 ], and single-wall carbon nanotubes [ 27 ], for instance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, noble metal/semiconductor hybrid materials show stronger SERS signal benefiting from higher aspect ratio and surface area [9,10]. Up to now, ZnO with different nano-morphologies has been widely studied [11][12][13][14][15], such as nanorods, nanosheets, nanowires, nanospheres, nanotubes and nanoflowers [16][17][18][19]. Especially, Ag nanoparticles supported on ZnO carrier are attractive.…”
mentioning
confidence: 99%